A comparative study about overweight and obesity in adolescents from two achool from Curitiba, Paraná - Rebello, Walker de Jesus (2007)
The present study was conducted to compare and determine the prevailing overweight and obesity of adolescents between a private and public school of Curitiba city, Paraná State, Brazil. A transverse cut off study was conducted with 517 adolescents, from age 10 to 14 years old, of both sexes, from a private and public schools of Curitiba city, Paraná State, in 2003.The overweight was expressed as Body Mass Index (BMI) equal or higher than 85 percentile (≥85°) and lower than 95 percentile(<95°), for age and sex. The obesity was defined as BMI equal or higher than 95 percentile (≥95°).The prevailing overweight and obesity of the two schools were 15.67% and 8.12%, respectively. A significant difference was observed in the prevailing overweight and obesity between the sexes of both schools. The prevailing overweight in males was 17.91% for the private school and 13.08% for the public school. The females prevailing overweight was 15.08% for the private school and 16.54% for the public school. The prevailing obesity in males for the private and public schools was 11.94% and 9.23%, respectively. The females prevailing obesity was 7.94% for private school and 3.15% for the public school. In this comparative study, significant differences in the prevailing overweight and obesity between the sexes of both schools were found, showing the great importance of this research, as the indexes of overweight and obesity in adolescents has been increasing year by year. There is a great necessity to detect and to intervene in this process with appropriate programs of physical activities and nutrition, as obesity has become a public health problem.